Відзначення 90-річчя створення в Україні системи державних архівних установ - Андрієвська, Л. (Архіви України, 2008)
The article on establishing Ukrainian state archives system in September, 1917 and its first

leaders displays the current situation in the archival sphere, highlights the preparation

activities for celebrations of the 90th anniversary of the state archives system of Ukraine on

September 14, 2007 in Kyiv.